2020
DOI: 10.1007/s10869-020-09714-3
|View full text |Cite
|
Sign up to set email alerts
|

It Takes More Than a Good Camera: Which Factors Contribute to Differences Between Face-to-Face Interviews and Videoconference Interviews Regarding Performance Ratings and Interviewee Perceptions?

Abstract: Due to technological progress, videoconference interviews have become more and more common in personnel selection. Nevertheless, even in recent studies, interviewees received lower performance ratings in videoconference interviews than in face-to-face (FTF) interviews and interviewees held more negative perceptions of these interviews. However, the reasons for these differences are unclear. Therefore, we conducted an experiment with 114 participants to compare FTF and videoconference interviews regarding inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 63 publications
2
60
0
1
Order By: Relevance
“…All other ANCOVAs remained significant. Furthermore, we also compared ratings from the interviewer with those from the second rater for the FTF condition directly because this is the same kind of comparison as in Basch et al’s (2020b) and Van Iddekinge et al’s (2006) studies. None of these comparisons reached significance, all ts < 1.48, all ps > 0.05.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All other ANCOVAs remained significant. Furthermore, we also compared ratings from the interviewer with those from the second rater for the FTF condition directly because this is the same kind of comparison as in Basch et al’s (2020b) and Van Iddekinge et al’s (2006) studies. None of these comparisons reached significance, all ts < 1.48, all ps > 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, Blacksmith et al’s (2016) meta-analysis found that, overall, interviewees react negatively to technology-mediated interviews in comparison to FTF interviews. Furthermore, evidence from a recent study by Basch et al (2020b) that compared perceptions of FTF and videoconference interviews confirmed that social presence is a mediator of the effects of the interview medium on interviewees’ fairness perceptions.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations